Search for large extra spatial dimensions in dimuon production with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (Amer Physical Soc, 2005)
We present the results of a search for the effects of large extra spatial dimensions in p (p) over bar collisions at root s = 1: 96 TeV in events containing a pair of energetic muons. The data correspond to 246 pb(-1) of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider. Good agreement with the expected background was found, yielding no evidence for large extra dimensions. We set 95% C. L. lower limits on the fundamental Planck scale between 0.85 and 1.27 TeV within several formalisms. These are the most stringent limits achieved in the dimuon channel to date.